Monitoring Kualitas Air Berdasarkan Parameter Fisika, Kimia, dan Biologi di Sungai Belimbing, Lombok Timur - Jupri, Ahmad; Aisyah, Nurul; Supardiono, Supardiono; Hidayati, Lilik; Fadli, Fadli; Husain, Pahmi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
River water quality monitoring is necessary to maintain the sustainability of aquatic ecosystems and ensure the availability of clean water. The Belimbing River in East Lombok Regency has the potential to experience quality decline due to domestic and agricultural activities in the surrounding area. This study was conducted in the dry season (April) and the rainy season (October) 2024 with sampling at three points (upstream, middle, and downstream). The sampling method used the grab sampling technique, with three replications at each point. Samples were stored in sterile bottles, placed in a cool box at a temperature of ±4°C, and analyzed a maximum of 24 hours after collection. The parameters analyzed included physical (TSS), chemical (pH, DO, BOD, COD, nitrate, and phosphate), and biological (fecal coliform). The analysis was carried out in the laboratory using the standard method SNI 6989.72:2009, with a UV-Vis spectrophotometer for nitrate and phosphate, an oven for TSS, and a titration method for BOD and COD. Fecal coliform analysis used the Most Probable Number (MPN) method. The results showed that most parameters exceeded the Class II water quality standards set by Government Regulation Number 22 of 2021, especially in the downstream area during the dry season. TSS values ​​reached 134 mg/L, BOD 12 mg/L, COD 115 mg/L, and fecal coliform 9,600 MPN/100 mL. The main sources of pollution were domestic waste, agricultural runoff, and poor sanitation. It can be concluded that the water quality of the Belimbing River indicates moderate to severe pollution. Integrated watershed management, community-based waste management, and environmental education are needed to sustainably restore the river's condition.